Socio-Cultural Life Of Kelud People In Connecting With Traditional Mitigation Effort Based On Local Wisdom - Sri Herminingrum; Esti Junining (Institute of Research and Community Service, University of Brawijaya)
Kelud is one of the 13 active volcanoes located in Java Island. The sequence of eruptions becomes a natural phenomenon which constructs the culture of the people who live around it. Therefore, this local wisdom-based research tries to investigate the relationship between the socio-cultural life of people inhibiting at the foot of Kelud Volcano and the disaster mitigation. The inhabitants of Sugihwaras Village who live within 10 km radius from the peak of Kelud are assumed as a “disaster-aware” community that becomes a valuable source of the local wisdom. The ethnography approach was stressed on the cultural tradition of the people of Sugihwaras that was observed directly from participation during traditional events, especially rituals. The rediscovery of the local wisdom in a traditional effort of disaster mitigation as the main goal of the research is expected to give contributions to good governance. This is highly possible because it is shown in most of the findings that the local wisdom of Kelud people teaches moral ethics which not only guides the relationship between human being and The Almighty, the way to respect each other among social human being, but also the harmonious life between human and nature. Keywords:Socio-cultural life, traditional mitigation, Kelud people, local wisdom